Soil Microbiomes From Fallow Fields Have Species-Specific Effects on Crop Growth and Pest Resistance - Howard, Mia M.; Muñoz, Christian A.; Kao-Kniffin, Jenny; Kessler, André (Frontiers in Plant Science, 2020)
Communities of microorganisms in the soil can affect plants’ growth and interactions with aboveground herbivores. Thus, there is growing interest in utilizing soil microbiomes to improve plant performance in agriculture (e.g., for pest control), but little is known about the phenotypic responses of various crop species to different microbiomes. In this study, we inoculated four crop species from different botanical families, maize (Zea mays, Poaceae), cucumber (Cucumis sativus, Cucurbitaceae), tomato (Solanum lycopersicum, Solanaceae), and lettuce (Lactuca sativa, Asteraceae), with diverse soil microbiomes originating from actively-managed agricultural fields or fallow fields under varying stages of succession (1, 3, and 16-years post-agriculture) sourced from a large-scale field experiment. We compared the crops’ responses to these different microbiomes by assessing their growth and resistance to two generalist insect pests, cabbage looper (Trichoplusia ni) and fall armyworm (Spodoptera frugiperda). These different microbiomes affected both plant growth and resistance, but the effects were species-specific. For instance, lettuce produced the largest leaves when inoculated with a 3-year fallow microbiome, the microbiome in which cucumber performed worst. Plants were generally more resistant to T. ni when inoculated with the later succession microbiomes, particularly in contrast to those treated with agricultural microbiomes. However, for tomato plants, the opposite pattern was observed with regard to S. frugiperda resistance. Collectively, these results indicate that plant responses to microbiomes are species-specific and emphasize the need to characterize the responses of taxonomically diverse plant species to different microbiomes.